Social Changes in the Development of Dhoho Kediri Airport from a Media Perspective - Mochamad Muchson; Vikas Kumar (The Journal of Society and Media, 2023)
The purpose of the study is to describe the social changes in the development of Dhoho Kediri Airport. The results show that these social changes are in the form of land acquisition (Bedol Dusun) to another place Tanjung Baru (physical changes). Communities also received compensation with a value far above the Selling Value of Tax Objects (NJOP) (economic changes), Rebuilding new clusters with much better economic conditions (social status). Invest the compensation money for land acquisition in the form of land, transport cars, livestock, and savings for school (social status). Even though the residents of Dusun Tanjung are no longer living in one area as before, they still maintain communication with each other (changes in social values). In Tanjung Baru, there is a good waste management system; in front of the house, there is a trash bin that the garbage workers will pick up every morning. This is different when the house has yet to be moved, which seems rundown because the garbage is placed in each yard (change in social norms). Organizational changes and community institutions have occurred, namely the movement of people from one RT or RW, prayer room, elementary, junior high school, kindergarten, and study center